Analisis Kompetensi Pengetahuan Dan Teknik Penilaian Pada Siswa Kelas VI Mata Pelajaran Bahasa Indonesia Di SDN GEMBONG 1 - Ina Magdalena; Khalisha Salsabila; Najwan Dennisa Yasmin; Tiara Dama Yanti; Tiara Nur Annisa (CV. ITTC INDONESIA, 2023)
Knowledge and assessment techniques for grade VI Indonesian language students at SDN Gembong 1 have an important role in ensuring an accurate evaluation of students' abilities. This study aims to analyze the knowledge competence and assessment techniques used by teachers in evaluating sixth grade students at SDN Gembong 1. This research uses a qualitative approach with the observation method of the teacher's assessment process and analysis of documents related to the curriculum and assessment guidelines. The results of the study show that teachers have sufficient knowledge about the assessment competencies that must be evaluated in class VI students, such as reading comprehension, writing, listening, speaking, and Indonesian language skills in general. In terms of assessment techniques, teachers use various assessment instruments, such as written tests, oral tests, projects, and portfolios. The teacher also applies observational techniques to evaluate students' speaking and listening skills. In addition, teachers also provide structured assignments that cover different aspects of the Indonesian language subject.